Efficiency enhancement of InP‐based inverted QD‐LEDs by incorporation of a polyethylenimine modified Al:ZnO layer. Issue 8 (15th September 2015) - Kim, Yohan; Ippen, Christian; Fischer, Bert; Lange, Alexander; Wedel, Armin
Abstract: We report efficiency enhancement of indium phosphide (InP) quantum dot‐based light‐emitting diodes (QD‐LEDs) by using an polyethylenimine (PEI) surface modifier. By adapting a solution processed PEI layer on top of a aluminum doped zinc oxide (Al:ZnO) nanoparticle (NP) film, the leakage current of the inverted device was substantially suppressed. In addition, the electron injection into the conduction band edge (CBE) of InP/ZnSe/ZnS QDs was also facilitated by the low work function (WF) of the Al:ZnO film which was realized by the strong interfacial dipoles of the thin film of PEI. As a result, the charge balance in the inverted devices was controlled by the change of surface roughness, the WF and the thickness of neighboring layers via spin‐coating the PEI dissolved in alcohol mixture on the Al:ZnO layer such that the current efficiency was dramatically increased from 0.07 cd/A to 3.17 cd/A. The performance of our device is not comparable to Cd‐based devices; however, it shows the great potential for using an interfacial dipole layer to develop highly efficient InP‐based inverted QD‐LEDs. Abstract : Current efficiency of indium phosphide (InP) quantum dot‐based light‐emitting diodes was improved from 0.07 to 3.17 cd/A by using a polyethylenimine surface modifier on top of an aluminum‐doped zinc oxide (Al:ZnO) nanoparticle film. The leakage current was substantially suppressed, and the electron injection into InP/ZnSe/ZnS quantum dots was also facilitated by the low work function of the Al:ZnO/polyethylenimine film.